Dual Role of Inflammasome Adaptor ASC in Cancer - Protti, Maria Pia; De Monte, Lucia (Frontiers in Cell and Developmental Biology, 2020)
Apoptosis-associated Speck-like protein containing a CARD (caspase activation and recruitment domain) (ASC), also called PYCARD/Target of Methylation-induced Silencing-1 (TMS1), was originally discovered as a protein that forms aggregates (“specks”) in human leukemia cells treated with chemotherapeutic agents. Its expression was found to be silenced by methylation in many human tumors, preventing tumor cells from undergoing apoptosis and supporting its role as a tumor suppressor. Subsequently, ASC was also identified as a central adaptor molecule of the inflammasome complex, which mediates the secretion of inflammatory cytokines (i.e., IL-1β and IL-18). Inflammatory cytokines have been shown to mediate tumor-promoting functions. Thus, in the context of cancer development and progression, ASC may exert opposing functions, i.e., be either tumor-suppressing by inducing tumor cell apoptosis, or tumor-promoting by favoring secretion of inflammatory cytokines (by tumor cells and/or tumor infiltrating myeloid cells) within the tumor microenvironment. Here, we report and discuss this dual role of ASC by also considering the final contribution of each of its two main functions in several cancer types, taking into consideration the correlation between ASC expression, clinical correlates, and patients’ survival. ASC and inflammasome targeting strategies are being developed. However, before the use of such treatments in clinical practice, it is fundamental to better dissect the role of ASC in different tumors, in order to privilege or avoid their use in those tumors in which ASC exerts an anti-tumor or pro-tumor function, respectively.